Digital Debt Labour: Migration, Deportation and Offshoring in Mexico - Enda Brophy; Rodrigo Finkelstein (tripleC: Communication, Capitalism & Critique)
This article explores the convergence of debt, deportation, and digital labour in Mexico by describing the making of a labour force working on the frontlines of transnational debt collection, performing what we call digital debt labour. Drawing on dozens of interviews in Tijuana and Mexico City conducted between 2016 and 2019, we relate the growth of a debt collection labour force in Mexico. To theorise the intersection between debt, migration, and digital labour, this article explores three overlapping, converging, and expanding forms of migration: debt migration, or the circulation of consumer credit through markets for, or processes of, debt collection; virtual migration or the outsourcing of call centre work to offshore locations and the return migration of call centre workers in the labour process; and forced migration, or the deportation of undocumented migrants. Our core argument is that this case study demonstrates the manner in which a highly financialised and digital variant of capitalism is evolving to develop a multi-faceted and opportunistic relationship with the growing trends of migration and deportation.